Robusta Coffee (Coffeacanephora) Decreasing IL-1Î± (Interleukin-1Î±) Expression and Increasing the Number of Fibroblasts in Healing Process in Dental Pulp in Wistar Rats - I Dewa Ayu Ratna Dewanti; I Dewa Ayu Susilawati; Pujiana Endah Lestari; Ristya Widi Endah Lestari; Erawati Wulandari; Roedy Budirahardjo; Dyah Setyorini; Sunlip Wibisono (Journal of Mathematical and Fundamental Sciences, 2019)
Fibroblasts and IL-1Î± are important components of inflammation and healing in dental caries. This healing allegedly could be enhanced by robusta coffee. The aim of this study was to investigate the effect of varying concentrations of robusta coffee on IL-1Î± expression and the number of fibroblasts. Wistar rats were used, divided into 4 groups and 3 subgroups (7-, 14"‘, and 21-day rats) with each group containing 4 animals: Control group: untreated group; 25% Coffee Group: cavities + treated with 25% coffee bean paste; 50% Coffee Group: cavities + treated with 50% coffee bean paste; 75% Coffee Group: cavities + treated with 75% coffee bean paste. The 7-, 14-, and 21-day rats were sacrificed serially for analysis of the number of dental pulp fibroblasts by staining with HE and IL-1Î± expression by immunohistochemistry. The resulting data were analyzed descriptively and using ANOVA, followed by an LSD test. The higher the concentration of robusta coffee, the more the expression of IL-1Î± decreased and the more the number of fibroblasts increased. It is suspected that immunomodulatory proteins inhibit IL-1Î± expression. It was concluded that robusta coffee could decrease IL-1Î± expression and increase the number of fibroblasts during the healing process in the dental pulp of Wistar rats.